Environmental Crime and Collaborative State Intervention - Pink, Grant; White, Rob.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This book examines the role and practical dynamics of governmental environmental law enforcement agencies and individuals who combat environmental crime. It will inform researchers about the 'real world' experiences of practitioners and provide an intellectual space for practitioners to examine critically what it is they do and why.
Keywords: Geography; Environmental geography; Nature conservation; Environmental policy; Criminology; Crime -- Sociological aspects; Environmental sociology; Geography; Environmental Geography; Crime and Society; Environmental Sociology; Nature Conservation; Environmental Politics; Criminology & Criminal Justice; Electronic books